“It’s kind of like an assault, you know”: media resisters’ meta-decoding practices of media culture. - Woodstock, Louise (Critical Studies in Media Communication, 2016)
Stuart Hall’s “Encoding/decoding” essay sparked an on-going focus in media studies on reception and audience studies that remains theoretically robust today. Hall’s insight that audience members decode media content in multiple ways, some in line with the dominant cultural ideology and some resistant to that ideology, illuminates the phenomenon of media resistance. Media resisters significantly limit their media consumption and they do so based on their decodings of media culture—decodings, or readings, that resist normative messages about commercialism and consumption, about the natural diffusion and inherent benefits of mobile technologies and social media, and about the political landscape depicted and generated by news media. Hall’s encoding/decoding model is expanded here to include not only audiences’ decodings of specific content, but of media culture broadly. Concerns about media culture in the aggregate lead to media resisters’ practices of limiting media engagement, practices themselves that are counter hegemonic.